1995
DOI: 10.1007/bf02349635
|View full text |Cite
|
Sign up to set email alerts
|

Low density lipoprotein receptors and polyamine levels in human colorectal adenocarcinoma

Abstract: The low density lipoprotein receptor (LDLR) is a cell surface protein that binds with LDL, providing the cell with cholesterol for new membrane synthesis. Rapidly growing cells have high numbers of LDLRs, and these proteins have also been detected in neoplastic samples of human colorectal mucosa. Polyamines, putrescine, spermidine, and spermine, play an important role in cellular growth, and studies on colorectal cancers have demonstrated higher polyamine levels in neoplastic mucosa samples than in surrounding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Cholesterol is mainly transported as plasma lipoproteins in an esterified form (31)(32)(33)(34)(35)(36)(37)(38)(39) to the brain tissue. Rapidly proliferating tumor cells show high cholesterol uptake via receptor-mediated endocytosis and have been shown to exhibit enhanced LDL receptor activity and large amounts of LDL receptors on the surface of each cell (40)(41)(42)(43)(44). Due to this reason, higher amount of cholesterol and cholesterol esters aggregate in the tissue of gliomas.…”
Section: Discussionmentioning
confidence: 99%
“…Cholesterol is mainly transported as plasma lipoproteins in an esterified form (31)(32)(33)(34)(35)(36)(37)(38)(39) to the brain tissue. Rapidly proliferating tumor cells show high cholesterol uptake via receptor-mediated endocytosis and have been shown to exhibit enhanced LDL receptor activity and large amounts of LDL receptors on the surface of each cell (40)(41)(42)(43)(44). Due to this reason, higher amount of cholesterol and cholesterol esters aggregate in the tissue of gliomas.…”
Section: Discussionmentioning
confidence: 99%
“…Rapidly dividing cells express high levels of LDL receptors. [21][22][23] In the absence of normal LDL receptors, the growth of the ascending aorta may be arrested in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that IT gastric cancer has a higher proliferative activity than DT gastric cancer, as demonstrated by the higher polyamine levels detected in IT compared with DT gastric cancer. 9 Moreover, the presence of LDLR has also been positively correlated with a higher polyamine content in colorectal cancer, 22 indicating its importance in cell proliferation and neoplastic transformation. It is known that IT gastric cancer develops in the areas of type III intestinal metaplasia, which present histological, biochemical, and functional features similar to those in colorectal mucosa.…”
Section: Discussionmentioning
confidence: 99%
“…14 Moreover, in the present study, the levels of LDLR protein were higher than the levels found in colorectal tumors, 17 in which the role of LDLR and its mRNA in colonic neoplastic growth has been extensively investigated. 17,[22][23][24][25] However, the distribution of LDLR in various normal human tissues and some solid tumors shows considerable variability. 12 Interestingly, among human tumors, only gastric carcinoma has higher 125 LDL binding than other tumors.…”
Section: Discussionmentioning
confidence: 99%